As an inhibitor of norepinephrine release, dexmedetomidine provides no improvement on stroke-associated pneumonia in mice - Zhou, Miaomiao; Luo, Qiong; Xu, Younian (Frontiers in Pharmacology, 2023)
Background: Dexmedetomidine (DEX) is commonly employed as a sedative agent to attenuate sympathetic tone and reduce norepinephrine (NE) levels. In the context of stroke-associated pneumonia (SAP), which is believed to arise from heightened sympathetic nervous system activity and elevated NE release, the precise influence of DEX remains uncertain. Methods: In this study, we generated an SAP model using middle cerebral artery occlusion (MCAO) and examined NE levels, immunological statuses in the brain and periphery, pneumonia symptoms, and extent of infarction. We aimed to determine the effects of DEX on SAP and explore the underlying. Despite its potential to reduce NE levels, DEX did not alleviate SAP symptoms or decrease the infarct area. Interestingly, DEX led to an increase in spleen size and spleen index. Furthermore, we observed a decrease in the CD3+ T cell population in both the blood and brain, but an increase in the spleen following DEX administration. The precise mechanism linking decreased CD3+ T cells and DEX’s role in SAP requires further investigation. Conclusion: The clinical use of DEX in stroke patients should be approached with caution, considering its inability to alleviate SAP symptoms and reduce the infarct area. Further research is necessary to fully understand the relationship between decreased CD3+ T cells and DEX’s influence on SAP.